NUMERICAL SIMULATION OF BIRDSTRIKE ON 19 PASSENGERS REGIONAL AIRCRAFT LEADING EDGE STRUCTURE - Prayoga - Nim: 13614067, Aditya
In aerospace field, birdsrtrike is frequently happened phenomenon and even regulated in safety regulation, in this case CASR 23. In CASR 23, eventhough it only regulates birdstrike cases at windshield and airspeed indicating system, studies about birdstrike at wing structure also need to be done. It is based on recommendation of reseacrh conducted by Atkins Limeted and FERA in 2008. Therefore, in this final project, a simulation of birdstrike case at 19 passengers regional aircraft wing was conducted, especially at the leading edge structure. Simulation was conducted to determine the response of the structure due to the collisions and investigate whether there was any structural damage after the collision. Explicit finite element method is used to simulate this case with LS-Dyna software. The numerical model of the bird used in this simulation is smooth particle hydrodynamic (SPH) model with hemispherical-ended cylinder geometry. Furthermore, the simulation result shows that with a bird mass of 0.9 kg, there is a structural damage at the leading edge due to the collision if the bird position is relatively perpendicular to the leading edge structure.